2016
DOI: 10.1111/jfs.12275
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salmonella, Escherichia Coli, Enterobacteriaceae and Aerobic Colony Counts Contamination Levels During the Beef Slaughter Process

Abstract: The study was conducted to determine the level of Salmonella, Escherichia coli, Enterobacteriaceae and aerobic colony counts (ACCs) contamination in beef carcass, equipment, slaughtermen hands and water at selected stages in abattoirs. Cattle carcasses were sampled at four sites (rump, neck, flank and brisket) from a low throughput (LTA) (n 5 240) and high throughput (HTA) (n 5 384) abattoirs. Using conventional biochemical tests, HTA yielded significantly higher ACC (5.2 log CFU/cm 2 ), E. coli (2.6 log CFU/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In studies conducted in South Africa, Turkey, Denmark, and Egypt, the prevalence of Salmonella was found to be 3%, 5%, 10%, and 33%, respectively [ 31 - 33 ]. However, there was no Salmonella detected in another South African study [ 34 ]. Salmonella is still among the top five foodborne pathogenic bacteria causing remarkable health problems to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in South Africa, Turkey, Denmark, and Egypt, the prevalence of Salmonella was found to be 3%, 5%, 10%, and 33%, respectively [ 31 - 33 ]. However, there was no Salmonella detected in another South African study [ 34 ]. Salmonella is still among the top five foodborne pathogenic bacteria causing remarkable health problems to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study strongly suggests some basic hygiene problems along the slaughter and processing chains, as ACC, TCC, and E. coli counts are standard methods for estimating the microbial contamination of carcasses [ 1 , 7 , 8 , 19 ]. In one study of Salmonella , Escherichia coli , Enterobacteriaceae, and aerobic colony count, during beef slaughter in the Eastern Cape Province of South Africa, washing did not reduce the microbial load in the carcass [ 17 ]. Studies elsewhere reported a similar finding that washing did not reduce the microbial contamination of meat [ 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies elsewhere reported a similar finding that washing did not reduce the microbial contamination of meat [ 18 , 20 , 21 ]. However, in many of the studies, a significant reduction in bacteria counts was only noted after the singeing, scalding, blasting, and chilling of meat [ 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] reported that few vendors practice the basics of using water and soap to wipe their equipment. Contaminated water spreads pathogens around thus increasing their proliferation [31]. The quality of water is vital as water plays a pivotal role during preparation of these ready-to-eat foods.…”
Section: Microbial Counts and Temperature In Raw And Cooked Meat Soldmentioning
confidence: 99%